Do they deserve it? The effect of consumer envy on brand attitude and choice - Ferreira, Kirla Seronni Cardoso (2018)
Envy has become popular as a marketing tool, and marketers are not only trying to evoke envy but also trying to convince consumers to use their products and brands to provoke envy in other consumers, so brands are strengthened. However, I demonstrate that malicious envy leads consumers to be more likely to choose a competing brand (analysis 2), and while benign envy increases consumers’ attitude toward a brand, malicious envy decreases their attitude toward a brand (analysis 3). Moreover, analysis 1 demonstrates that the effects of deservingness on malicious envy has a moderator factor (type of relationship) that affects how undeservingness is perceived, in terms of luck and deceit. The objective is to investigate the influence of deservingness and type of relationship (like or dislike a person) on benign and malicious envy, and the role of such envy subtypes on brand choice and brand attitude. The findings introduce a more nuanced view of the undeservingness effects and type of relationship, and contribute to the literature on brands and emotions, showing that each envy subtype brings different consequences for brands.